Pengembangan Strategi Pada Aktivitas Rantai Nilai Panas Bumi (Studi Pada PT Geo Dipa Energi (Persero)) - Ayuningtyas, Maharani; Harianto, Harianto; Safari, Arief (JURNAL BISNIS STRATEGI, 2019)
Indonesia's geothermal potential is the second largest in the world. But in fact, the magnitude of its geothermal potential has not been utilized optimally. With investments and risks that are quite high, and a relatively long period of time makes investors do not much invest in this energy sector. Especially with the presence of single buyer, in this case is PT PLN (Persero). The issue of power purchase agreement between developers and PT PLN (Persero) is still become the biggest obstacle to the development of geothermal power plant. This study aims to formulate an appropriate strategy priority used by PT Geo Dipa Energi (Persero) in producing the optimal cost of generating electricity based on Minister of Energy and Mineral Resources Regulation Number 50 of 2017 concerning Utilization of Renewable Energy Sources for Electricity Supply. Data collection uses judgment sampling techniques. External environmental analysis is carried out through PESTLE analysis, while internal environmental analysis is carried out through value chain analysis. TOWS analysis is conducted to provide an alternative strategies, that from choices of alternative strategies will be prioritized using AHP analysis. The results of the study produced the chosen strategy priority that is to conduct intensive coordination with PT PLN (Persero) in negotiations to develop a new prospect area.